Pemberdayaan Peternak Milenial Desa Mundu Klaten Dalam Pemanfaatan Limbah Biogas Menjadi Pupuk Organik Padat Sludge - Arif Rahman Hakim; Emi Widiyanti; Erma Listiyaningsih; Putri Nur Khasanah; Dion Pratama Ramadhan (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service activity was carried out with the aim of empowering Kelompok Tani Ternak Margo Mulyo 3 in utilizing biogas waste into solid sludge organic fertilizer. The hope of this activity is to help partner communities in dealing with biogas waste which is very abundant and has not been utilized optimally. The implementation method is through a group community empowerment approach. This activity includes 5 methods, namely initial evaluation, training, direct practice, packaging competition, and final evaluation. This community empowerment succeeded in initiating a new business start-up, namely biogas sludge organic fertilizer by providing assistance in the process of making biogas sludge organic fertilizer and testing the content of biogas waste to see whether it meets the established standards for organic fertilizer content. This community empowerment activity has had a positive impact, namely economic benefits for the KTT Margo Mulyo 3 Millennial.